Nature and Extent of Corporate Social Responsibility Disclosure in India: A Study of Selected BSE Companies. (March 2020) - Aspal, Parvesh Kumar; Singh, Manjit
Corporate social responsibility (CSR) disclosure is growing at an increasing trend in the corporate world. It is a relatively new concept and it has emerged as a crucial research domain over the last decade. Financial as well as social performances of the company are the strong basis of sustainable development. At present, corporations in India are confirming an authentic and legitimate concern about the upliftment of their stakeholders and community. Thus, the prime objective of this study is to analyse the nature and extent of CSR disclosure in Indian companies selected from the top 200 BSE companies for the period 2014–2016. Content analysis has been employed using CSR checklist to compute the disclosure score under four dimensions of CSR, such as employee relations; welfare and development of community; consumer issues and products and environment. The percentage of companies disclosing CSR has been observed to be enhancing over the period of study and regarding the dimensions of CSR. The most disclosed dimension is customer issues and products followed by community development and welfare, environment and employee relations. The analysis also reveals that the CSR disclosure in selected industries has been increased during the period of study. Oil and gas industry is on the top position in terms of CSR disclosure and chemical and leather industry stands at the bottom-most position.